2010
DOI: 10.1038/ncomms1021
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam-assisted superplastic shaping of nanoscale amorphous silica

Abstract: At room temperature, glasses are known to be brittle and fracture upon deformation. Zheng et al. show that, by exposing amorphous silica nanostructures to a low-intensity electron beam, it is possible to achieve dramatic shape changes, including a superplastic elongation of 200% for nanowires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
275
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 299 publications
(288 citation statements)
references
References 49 publications
9
275
4
Order By: Relevance
“…As shown in Figure 13 , fractures were generated in an Al 2 O 3 NW loop when it was examined during TEM imaging 146. Previous studies have also shown that EBI may increase the plasticity of NaCl,142 SiO 2 138 and Si NWs,147 weaken the strength of Al 2 O 3 NWs,146 stiffen zinc tin oxide NWs,148 and significantly decrease the fatigue life of ZnO NWs 149. Also, EBI during SEM imaging may generate pits in the shell structure of carbon nanotubes 150.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 90%
See 3 more Smart Citations
“…As shown in Figure 13 , fractures were generated in an Al 2 O 3 NW loop when it was examined during TEM imaging 146. Previous studies have also shown that EBI may increase the plasticity of NaCl,142 SiO 2 138 and Si NWs,147 weaken the strength of Al 2 O 3 NWs,146 stiffen zinc tin oxide NWs,148 and significantly decrease the fatigue life of ZnO NWs 149. Also, EBI during SEM imaging may generate pits in the shell structure of carbon nanotubes 150.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 90%
“…Thermal effect and knock‐on effect from energetic electrons in TEM or SEM may contribute to NW specimens damage 136. Thermal effect induced by energetic electrons is difficult to quantify, however recent studies have revealed that the temperature increase of a NW sample during a normal TEM imaging process is far below 100 °C 99, 102, 137, 138. Therefore thermal effect should insignificantly alter the properties of NWs.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
See 2 more Smart Citations
“…The accelerating voltage of the electron gun was set to be 10 kV during the test in order to reduce the potential beam damage. The contact pressure was defined as the applied force divided by the contact area between the particle and substrate assuming a perfect circular contact [10][11][12], and the compression ratio was defined as the compressive displacement (u) (after subtracting the contribution from the substrate) divided by the particle diameter (D) in our study. The H c was defined as the contact pressure at the point of yield for brittle particles or the peak contact pressure for ductile particles.…”
Section: In Situ Mechanical Test and Data Analysismentioning
confidence: 99%